Synthesis of highly twinned ZnSe nanorods for enhancing N2 electrochemical conversion to NH3. Issue 17 (8th February 2023) - Qiu, Kangwen; Han, Yuning; Guo, Wenbo; Wang, Licun; Cheng, Jinbing; Luo, Yongsong
Abstract : Highly twinned ZnSe nanorods with abundant surface atomic steps were prepared by anion exchange for the enhanced N2 electrochemical conversion to NH3 . Abstract : In this work, we report an atomistic understanding of the hydrogenation behavior of a highly twinned ZnSe nanorod (T-ZnSe) with a large density of surface atomic steps and the activation of N2 molecules adsorbed on its surface. Theoretical calculations suggest that the atomic steps are essential for the hydrogenation of T-ZnSe, which greatly enhances its catalytic activity. As a result, the T-ZnSe nanorods exhibit a significantly enhanced NH3 production rate of 13.3 μg h −1 mg −1 and faradaic efficiency of 5.83% towards the NRR compared with the pristine ZnSe nanorods. This report offers an important pathway for the development of efficient catalysts for the NRR, and a versatile anion-exchange strategy for efficiently manipulating materials' functionalities.